1990
DOI: 10.1136/jnnp.53.11.972
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of predictions about progress of patients on a stroke unit.

Abstract: The aim of the study was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 14 publications
(2 reference statements)
1
16
0
Order By: Relevance
“…Finally, 13 studies validated a prediction model with that of a second stroke group or were specifically focused on validation [40,41,99] or improvement [85] of an already published prediction model in an independent cohort.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 13 studies validated a prediction model with that of a second stroke group or were specifically focused on validation [40,41,99] or improvement [85] of an already published prediction model in an independent cohort.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the analysis of internal, statistical and external validity are summarized in Table II. Four of these involve validation studies of pre-existing prediction models {40, 41,85,99].…”
Section: Resultsmentioning
confidence: 99%
“…Calculating the percentages of the number of patients who returned to work, we found that 37.50% had a left hemisphere lesion with nonfluent aphasia; 15 …”
Section: Return To Workmentioning
confidence: 99%
“…The same group 45 has provided a lucid summary of what these stroke outcome studies and formulas can and cannot illuminate. Formulas and correlations only have actuarial (ie, group) significance; they have weak predictive power for individuals.…”
mentioning
confidence: 99%